2019
DOI: 10.1016/j.pmedr.2018.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns among French-speaking men residing in Montreal, Canada

Abstract: The purpose of this study was to describe dietary patterns among 1636 French-speaking men residing in Montreal, Canada and to assess sociodemographic and lifestyle characteristics of men adhering to the dietary patterns identified. Participants were population controls from the Prostate Cancer and Environment Study, a case-control study conducted between 2006 and 2011 in Montreal. Information on diet was collected using a food frequency questionnaire, and principal component analysis, a data-driven method and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 37 publications
2
13
0
Order By: Relevance
“…Associations with education level can be characterized generally as an increase in adherence to the "Rational" DP and a decrease in the "Salt" and "Meat" DPs with increasing education level. This tendency corresponds to the literature data from other countries [45,50,[56][57][58][59] and is usually explained by the lack of knowledge, culinary skills, and motivation among people with lower levels of education [2].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Associations with education level can be characterized generally as an increase in adherence to the "Rational" DP and a decrease in the "Salt" and "Meat" DPs with increasing education level. This tendency corresponds to the literature data from other countries [45,50,[56][57][58][59] and is usually explained by the lack of knowledge, culinary skills, and motivation among people with lower levels of education [2].…”
Section: Discussionsupporting
confidence: 86%
“…On the other hand, a number of studies showed the ambiguity of these tendencies. For example, a Canadian study of French-speaking men in Montreal showed high adherence of those having a family to a modified Western-Salt DP, which included, among other products, large amounts of beef, pork, chicken, hot dogs or sausages, cold cuts, bacon, and grilled food [50]. These data resemble the information obtained in this study.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…However, these recalls generally involve a limited number of days and gather data only on short-term dietary intake [18]. The food frequency questionnaire (FFQ) is usually used to evaluate long-term dietary intake [19][20][21]. Studies have shown that the FFQ is the most feasible and cost-effective tool when compared to other dietary assessment methods [18].…”
Section: Introductionmentioning
confidence: 99%